Paradise Lost Dressed in the Costume of History: John Martin’s Rendition of Paradise Lost - Atashi, Laleh; Anushiravani, Alireza (k@ta: A Biannual Publication on the Study of Language and Literature, 2012)
The story of the loss of paradise has been read and interpreted in different ages. Commentary on Milton’s Paradise Lost is not limited to verbal texts; painters and illustrators have contributed greatly to the poem by presenting their own time-bound readings and interpretations of the poem through their illustrations that are far beyond mere decorations. John Martin, in the aftermath of the Industrial Revolution, deletes the Father and the Son from his illustrations. Only angels such as Raphael are the representations of deity and are as powerless and tiny as Adam and Eve. Adam and Eve, after the Fall seem as small, powerless and as subjugated to the natural surrounding as they were before the Fall. Satan is the only powerful figure in his elegant palace. Through a new historical outlook, the researchers aim at exposing the workings of ideology and dominant discourses that informed John Martin’s pictorial reading of Milton’s poem in the early 19th century